'Trial by fire': An online survey exploring confidence of junior doctors in managing toxicology presentations to the emergency department. (18th August 2022) - Smith, Jennifer L.; McCutcheon, David; Weber, Courtney; Soderstrom, Jessamine; Burcham, Jonathon; Fatovich, Daniel M.
Abstract: Introduction: The often unknown nature of acute drug intoxication, especially with illicit drugs and emerging novel psychoactive substances, can present a significant challenge for emergency clinicians. Less experienced clinicians are particularly vulnerable to the diagnostic dilemmas of complex toxicology emergencies. We sought to better understand the confidence of junior doctors in assessing and managing toxicological emergencies across two emergency departments in Perth, Australia. Methods: An online survey was conducted between August 2020 and February 2021. Self‐rated confidence was measured on a five‐point Likert Scale across 10 statements. Two open‐ended questions were included to capture perceived barriers and facilitators impacting clinical confidence. Quantitative data were analysed using descriptive methods and Fisher's exact test. Free‐text responses were analysed using content analysis. Results: A total of 104 surveys were completed (19.2% interns, 40.4% resident medical officers and 40.4% registrars). Self‐rated confidence varied across statements and by staff type. The lowest confidence rating was for managing a patient who had overdosed from an unknown substance (31.7%) and the highest rating for referring a patient to psychiatry following deliberate self‐poisoning (86.6%). Confidence increased with greater clinical experience for all statements. Qualitative analysis revealed perceptions of clinical preparedness, complexity of patients and a safe and supportive culture as key factors impacting confidence. Discussion and Conclusions: Overcoming perceived deficits in knowledge and clinical experience were key to building confidence. Our findings highlight the need for improved access to toxicology‐specific curricula and training, and strategies to ensure adequate supervision from senior clinicians.